Design and implementation of CNFET-based universal bi-quad filter and quadrature oscillator utilizing innovative floating current source (IFCS) - Arsen Ahmed Mohammed; Ahmed Burhan Mohammed; Zaidoon Khalaf Mahmood (Results in Engineering)
This study presents, simulation study and a design of voltage mode Universal Bi-quad Filter (UBF) and a Quadrature Oscillator (QO) based Innovative Floating Current Source (IFCS) using Carbon nanotube field effect transistor (CNFET) transistor technology. The technique here described takes advantage of the intrinsic features-a scalability, a low power dissipation has the range of the supplied voltages is ±0.1 V and outstanding performances-of CNFET devices to implement both the topologies of UBF and QO. The UBF has been designed in order to guarantee a large number of filtering responses, namely, (low-pass, high-pass, band-pass, and band-stop), all tunable electrically with respect to the natural frequency and quality factor. The QO has been obtained from the UBF by modifying it in such a way as to get self-regulated control on the oscillation frequency and amplitude. This design focuses on power efficiency while keeping performance high, thus enabling it for integration in a monolithic integrated circuit. The suggested CNTFET-IFCS demonstrates power consumption that is 6000 times lower than silicon CMOS semiconductors using 32 nm transistor parameter, along with a substantial decrease in chip dimension. All simulations were conducted utilizing Cadence Virtuoso tools.